DAMPAK FLUKTUASI EKONOMI GLOBAL TERHADAP PENGELOLAAN PORTOFOLIO INVESTASI DAN RETURN SAHAM DI BURSA EFEK INDONESIA - Anwar Arifin Pinem; Siti Rahmayuni (Income, 2025)
This study aims to analyze the impact of global economic fluctuations on investment portfolio management and stock returns in the Indonesia Stock Exchange (IDX). Global economic fluctuations, represented by macro indicators such as global inflation, the Federal Reserve’s interest rate, world oil prices, and the USD/IDR exchange rate, have a significant influence on the behavior of the Indonesian capital market. This research employs a quantitative approach with an explanatory design. The population consists of companies listed on the IDX, with the LQ45 index selected as the sample using purposive sampling, supported by secondary data such as stock index reports, exchange rates, and macroeconomic data. The results indicate that global economic turbulence tends to increase stock market volatility, which affects portfolio management strategies. Investors need to adopt asset diversification, risk management, and hedging strategies to minimize losses. These findings emphasize the importance of financial and economic sensitivity in facing global uncertainty to achieve investment return optimization.